Sustainable product development in practice: an international survey. Issue 6 (1st July 2014) - Kara, Sami; Ibbotson, Suphunnika; Kayis, Berman
Abstract : Purpose: – Improved environmental performance of products and services have lately become one of the main strategic and operational goals of manufacturers. This is due to influences from various stakeholders including government, consumers, societies and the business partners. Evidently, different manufacturers differently implement their environmental practices for sustainable product development depending on various driving factors such as customer awareness, legislation, economic benefits and competitive strategies, etc. In theory, manufacturers can efficiently undertake sustainable product development by implementing life cycle thinking into their system. This way, they can monitor the environment hot spots throughout a product life cycle and be able to minimise the environmental impact effectively. Therefore, several researchers have focused on developing tools and strategies to support the manufacturers in implementing sustainable manufacturing and product development studies. However, in reality, each manufacturer may operate their manufacturing system differently to accommodate different demands and constraints induced by firm characteristics and its regional location. Their attempts to implement the sustainable tools and strategies to their companies would also be different. Thus far, a number of studies have studied the implementation for a specific company. No studies have examined the relationship between their decisions and implementation for different characteristics of firms and different manufacturing locations. Therefore, the purpose of this paper is to comprehensively investigate the practices of manufacturers towards sustainable product development. Design/methodology/approach: – A detailed statistical analysis was conducted on the survey data gathered from 330 manufacturing organisations in 13 countries. The research questions mainly cover implementation approaches, decision tools and techniques used and main driving forces at the strategic and operational levels concerning environmental practices in sustainable product development. This is to bridge the gaps between the research outputs and implementations in practice for the developed sustainable strategies and tools. Results highlighted interesting relationships of the implementations across different geographical regions (locations) as well as types and sizes of manufacturers. They can be used to shed some light for future research direction, the dominant driving forces of consumers and regulations importance towards the manufacturer practices to improve not only the environmental performance but also their social responsibility. In total, 12 null hypotheses were formulated to test the relationships as well as the correlations between the manufacturing characteristics and the research questions which cover several driving forces in implementing the environmental strategies. Findings: – The results of this large-scale global research highlighted that different geographical/manufacturing regions are driven mainly by legislation, competition and consumer pressures whilst manufacturers of different sizes utilise various decision tools. Design tools such as LCA, DFE and ECQFD methods are likely to be utilised in the medium-and high-complexity product development by OEM and ETM manufacturers. Environmental responsibility plays an important role and also enhanced by other driving forces such as the economic benefits, the long-term survival in the market and the company image. Research limitations/implications: – Future work may include some or all of the following; such as respondents of this survey may be re-contacted and comparative data can be gathered from these manufacturers to capture the changes over the years. Further investigation of the sustainable supply chain management approaches, influences of dynamic driving forces and the environmental practices towards cleaner production practices such as improving energy efficiency, minimising waste, recycling scraps and reusing product as well as the product recovery practices for used products would be beneficial to gather and evaluate. This would support to address the current trends and emerging practices. Practical implications: – Results highlighted interesting relationships and thus provide some answers on strategies adopted by many manufacturers for the sustainability approaches and implementations across different geographical regions (locations) as well as types and sizes of manufacturers. The wave of change towards sustainability is clearly on enterprises, industries, communities and governments for thinking about solutions to increase the awareness in environmental sustainability thus reduce carbon footprint. In some areas there is clear progress but for many, this process is just beginning. Social implications: – There is an overwhelming amount of information, methods and opinions, and proliferation of initiatives. It is in this climate that not only manufacturers but society must provide a practical and effective way to develop and disseminate the skills and knowledge required to fuel an environmentally sustainable economy. To achieve this, results of global surveys like this paper may support manufacturers who need to work with communities and stay well connected to their stakeholders. This may lead to developing training packages that accurately reflect industry needs and provide leadership in communities and workforce development. Originality/value: – There is generally an understanding of the sustainable product development and the use and role of tools and techniques to improve environmental performance of manufacturers at micro-level (within companies based on selected product, process, environmental tools and manufacturing characteristics). Whereas, a large-scale research like this paper, to present the status of sustainable product and process development approaches used by manufacturers located around the globe, of different sizes, types within existing operational and corporate strategies and eco-design initiatives have not been detailed.